Process development for fabrication of organic thin film transistors - Mei, Ting. (2012)
Organic semiconductors are deemed as suitable candidates for implementing both circuits and displays on plastic. Transistors made from organic materials have the advantages of low cost, flexibility and reduced thermal budget during device processing.